2019
DOI: 10.3390/su11174657
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Crop Yields and Their Extreme Value Analysis over India

Abstract: Trends of rice, wheat, maize, sorghum (jowar) and pearl millet (bazra) yields of India are studied in relation to water irrigation for the period 1951 to 2012. These crop yields have been subjected to correlation with the Normalized Difference Vegetation Index (NDVI), obtained from NOAA Advanced Very High Resolution Radiometer (AVHRR) (for 1982 to 2000) and Moderate Imaging Spectroradiometer (MODIS) Terra (for 2001 to 2012) to understand the linear association among them. Crop products and food inadequacy in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…These projected changes are still well below acceptable global standards to achieve food security. The above finding agrees with [38], where it was reported that due to the predicted increase in food demand worldwide by 2050, there must be incremental yield, needing more to be done to meet the targeted approximate 20% increase in the yield of crops to tackle food sufficiency. Research [34] also concluded that the net impact of climate change on oil palm yield in the Niger Delta region of Nigeria is positive, in line with the positive effects of climate change on the yield of crops considered for this study.…”
Section: Soybeansupporting
confidence: 89%
“…These projected changes are still well below acceptable global standards to achieve food security. The above finding agrees with [38], where it was reported that due to the predicted increase in food demand worldwide by 2050, there must be incremental yield, needing more to be done to meet the targeted approximate 20% increase in the yield of crops to tackle food sufficiency. Research [34] also concluded that the net impact of climate change on oil palm yield in the Niger Delta region of Nigeria is positive, in line with the positive effects of climate change on the yield of crops considered for this study.…”
Section: Soybeansupporting
confidence: 89%
“…The city of Bengaluru has experienced a rapid expansion over the last decades, which have seen it growing into a mega city with over 10 million inhabitants (Government of India, Ministry of Home Affairs, 2011;Narayana, 2011). This resulted in a transformation of the agricultural production toward more intense crop management practices associated with higher fertilization rates (Bora, 2022) and increased irrigation (Mishra et al, 2020;Sankar et al, 2011) which led to higher annual crop yields in rural and urban areas (Government of Karnataka, 2007Karnataka, , 2011Karnataka, , 2014bLakshmi Kumar et al, 2019;Ritchie et al, 2022). On the other hand, the city has been facing serious challenges to meet the growing water demand, and groundwater resources have been over-exploited, which has led to the main river in the Arkavathy catchment to dry up since 1990 (Raj, 2016;Srinivasan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%